AW-AD-1: SEASONAL VARIATION IN DAY-BY-DAY BLOOD PRESSURE VARIABILITY AND ITS EFFECT ON CARDIOVASCULAR OUTCOMES. (January 2023) - Narita, Keisuke; Hoshide, Satoshi; Kario, Kazuomi
Abstract : Although day-by-day home blood pressure (BP) variability has been associated with cardiovascular disease (CVD) risk, it remains unclear whether this association differs from season to season. The present study aimed to assess seasonal variation in day-by-day home BP variability (BPV) and its association with CVD risk. We analyzed the data from a nationwide, prospective observational study, the J-HOP (Japan Morning Surge-Home Blood Pressure) study, in which 14 consecutive days of home BP monitoring were conducted. The values of standard deviation (SDSBP), coefficient of variation (CVSBP), and average real variability (ARVSBP) of home systolic BP (SBP) were used as indices of day-by-day home BPV. Among 4231 participants (mean age, 64.9 ± 10.9 years, 46.7% male, 91.5% hypertensives), all three day-by-day home BPV indices were lower in summer than winter after adjusting for confounding factors. In winter, SDSBP, CVSBP, and ARVSBP were significantly associated with increased risk of CVD events (coronary artery disease, stroke, heart failure, and aortic dissection) (adjusted HR [95%CI] per 1-SD of SDSBP, 1.27 [1.03, 1.56]; CVSBP, 1.25 [1.03, 1.53]; ARVSBP, 1.44 [1.18, 1.77]). These relationships were also observed in the analysis of quartiles of BPV parameters (adjusted HR [95%CI] compared to the 1st quartile, 4th quartile of SDSBP 2.25 [1.05, 4.81]; CVSBP 2.91 [1.40, 6.03]; ARVSBP 2.71 [1.25, 5.89]). In other seasons, however, there were no significant associations between day-by-day home BPV and CVD event risk. Our findings indicate that day-by-day home BPV measured in winter is more strongly associated with future CVD incidence than that measured in other seasons.